PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF IPA BERBASIS MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATERI GAYA DI KELAS IV SD NEGERI 101776 SAMPALI - Annisa, Nurul; Simbolon, Naeklan (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to: (1) find out the feasibility of interactive learning media based on learning modelGuided Inquiry on Style material in class IV SD Negeri 101776 Sampali and (2) to know the effectiveness of using interactive media based on learning modelGuided Inquiry on the material of Style in class IV SD Negeri 101776 Sampali FY 2017/2018. This type of research is a development research using the Borg and Gall product development model combined with the Dick and Carey development model. Trial subjects consisted of 3 students for individual testing, 9 students for small group testing, and 29 students for limited field testing. Based on hypothesis test result using t test with significance level (Î± = 0,05) obtained titung 2,76 and ttabel 2,001. From these results, it is known that thitung â¥ t table shows there are differences in learning outcomes between students using interactive learning media based on guided inquiry model (guided inquiry) with students using guided inquiry model (guided inquiry) and textbooks.Keywords: Development Of Interactive Learning Media, IPA, Model Guided Inquiry.